The article Social Criticism[ in the short story of Orang Gila Yang Bijak Dan Merdeka by Jefta H. Atapeni.: Kritik Sosial Dalam Cerpen Orang Gila Yang Bijak Dan Merdeka Karya Jefta H. Atapeni - Baksuni, I'm ester; Hayon G. Nico; Margaretha P.E Djokaho; Karolus B. Jama (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2022)
This study raises about the social criticism contained in the short story Orang Gila Yang Bijak dan Merdeka by Jefta H. Atapeni. The problem raised in this study is social criticism and the form of delivery of social criticism in the short story of Orang Gila Yang Bijak dan Merdeka by Jefta H. Atapeni. This study aims to describe social criticism and the form of delivery of social criticism in the short story Orang Gila Yang Bijak dan Merdeka by Jefta H. Atapeni. This study uses Antonio Gramsci's theory of Domination and Hegemony. The method used in this research is descriptive qualitative research method. The source of the data in this research is the short story of Orang Gila Yang Bijak dan Merdeka by Jefta H. Atapeni. The results of this study are: 1) The most dominant social criticism discussed is socio-economic criticism, while the dominant form of criticism that appears is a symbolic and simple form of criticism. 2) Social criticism includes, social criticism of political, economic, cultural, religious, morality, gender, power, and government issues. 3) The forms of delivery of criticism include direct criticism, namely in a straightforward manner, indirect forms, namely, symbolically, subtly, and cynically. The results of this study are expected to be useful for broadening the horizons of appreciation of literary readers for social criticism in literary works in the form of short stories and its application with Antonio Gramsci's theory of Domination and Hegemony. The results of this study are also expected to be used as reference material and as a reference or comparison material for literary researchers in the future.